5S Practice: its effects on quality and productivity of work among UiTM support staff / Wan Noorli Razali, Zuraira Libasin and Rosley Jaafar - Razali, Wan Noorli; Libasin, Zuraira; Jaafar, Rosley (2020)
As a country with Muslim majority population, Indonesia is a potential market for the development of the Muslim fashion industry. However, this opportunity has not been utilized optimally due to the limited ability to understand customer needs and desires and the lack of Islamic small-business fashion knowledge in determining strategies that can be used to improve Marketing Performance (MP). Thus, this study aims to improve marketing performance in Islamic small business fashion by increasing marketing capability. Three dimensions of marketing capability were used in this study, namely marketing innovativeness (MI), market sensing capabilities (MSC), and Customer Relationship Management Capabilities (CRMC). Previous studies have shown that there are inconsistencies in findings that examine the relationship between marketing capability and marketing performance. Theoretically, marketing capability is a strategic tool for improving marketing performance, but practically the marketing capability dimensions do not always produce better marketing performance. Therefore, this study proposes a Religio-Centric Marketing Communication Strategy (RMCS) as a variable that mediates the relationship between marketing capability and marketing performance. RMCS is a new variable that was formed from the collaboration between marketing communication strategy and religio-centric concepts. RMCS is a marketing communication strategy that is carried out religiously when communicating with other parties. The population in this study are owners or managers of Islamic small business fashion in Indonesia. Data were obtained from questionnaires distributed to 310 selected respondents and then analysed by using Structural Equation Model (SEM) with AMOS. The results showed that MP can be increased through MSC, CRMC, and RMCS, but MI was apparently unable to increase MP. Meanwhile, optimizing RMCS can be done through MI, MSC, and CRMC. From these results, it can be concluded that the performance of Islamic small business fashion can be improved through marketing communication strategies in a religious manner when communicating with other parties.